InGaN Laser Diodes-Gain, Spectra and Nonlinear Dynamics - Hassan, Nahid; Imran, Sazzad M S (Dhaka University Journal of Applied Science and Engineering, 2023)
In this era, short-wavelength laser diodes with quantum-well (QW) structures offer plenty of opportunities for improvement in laser performance and receive widespread attention. Therefore, we develop dynamic model of the violet-blue InGaN laser diodes (LDs) and discuss basic features of the device in this paper. We investigate longitudinal mode dynamics through detail numerical simulation of the rate equation model of the quantum-well LDs. We selectively observe several effects such as relaxation oscillation, mode competition, intensity noise etc. From the dynamic behavior of the gain spectrum and time-varying modal photon numbers we found that the higher intensity noise of the quantum-well structure was due to random fluctuation with time among the different modes. The results were explained considering the previously published findings to confirm the validity of the proposed rate equation model of the quantum-well structures. DUJASE Vol. 7 (2) 62-67, 2022 (July)